CULTURE TOURISM IN GAZIANTEP AND ITS SURROUNDING AREA - Sibel OZUTURK (EPRA International Journal of Multidisciplinary Research (IJMR), 2023)
This study named "Culture Tourism in Gaziantep and its immediate environment", contains historical and cultural attractions that create the basis of culture tourism in Gaziantep and the presentation possibilities to the tourist with respect to gradually developing understanding of tourism. Therefore, as an alternative tourism type, culture tourism, is a kind of tourism experienced on cultural resources, and its main motivation is to see and know new places, to learn new things and the most important is that, it creates a need for gaining new experiences to participate in cultural facilities. In this study, available cultural and historical attractions in Gaziantep province in South-Eastern Anatolia region are emphasised. In this respect, historical and cultural heritage attractions, in Gaziantep province, which still continue to exist and belong to Hittite, Med, Assyria, Persian, Iskender, Seleskos, Roman, Byzantine, Islamic-Arabic and Islamic-Turkish culture are explained. Moreover, attractions are categorized under 5 different main subject areas such as historically, prehistorically, archeologically, military and religion. Later, the tourism capacity of the examination area is emphasised and in the last part of the study general suggestions on the improvement and organization of cultural tourism are given.